2013
DOI: 10.1186/1471-2180-13-168
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of an Araucaria angustifolia (Coniferopsida) fungal seed pathogen, Neofusicoccum parvum, by soil streptomycetes

Abstract: BackgroundAraucariaceae are important forest trees of the southern hemisphere. Life expectancy of their seedlings can largely be reduced by fungal infections. In this study we have isolated and characterized such a fungus and investigated the potential of Streptomyces Actinobacteria from the respective rhizosphere to act as antagonists.ResultsThe pathogenic fungus from Araucaria angustifolia seeds was identified by morphological markers (pore-associated Woronin-bodies) as belonging to the Pezizomycotina. Molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…chloramphenicol, streptomycin) and antifungal (i.e. chitinase) compounds (Akagawa et al 1975;Distler et al 1987;Dalmas et al 2013;Awad et al 2014). Also, Arthrobacter species, which belong to the Micrococcaceae family, have been found to produce antifungal compounds such as dimethylhexadecylamine (Velazquez-Becerra et al 2013).…”
Section: Bacterial Community Reassembly and Disease Suppressionmentioning
confidence: 99%
“…chloramphenicol, streptomycin) and antifungal (i.e. chitinase) compounds (Akagawa et al 1975;Distler et al 1987;Dalmas et al 2013;Awad et al 2014). Also, Arthrobacter species, which belong to the Micrococcaceae family, have been found to produce antifungal compounds such as dimethylhexadecylamine (Velazquez-Becerra et al 2013).…”
Section: Bacterial Community Reassembly and Disease Suppressionmentioning
confidence: 99%
“…In a similar fashion, even though beneficial bacteria inhabiting the rhizosphere and/or the endosphere of plants and their secondary metabolites have been put forward by some authors to reduce grapevine pathogen diseases [6], information reported in the literature is limited [8,9,10,11,12]. These biocontrol agents, such as Streptomyces spp., would affect pathogen performance by antibiosis, competition for niches and nutrients, interference with pathogen signaling, or by stimulation of host plant defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Each culture is treated as a monoculture, whilst exploiting co-culture characteristics. Approaches here include: membrane segregation [88] including dialysis/hydrogel system [90], transwell systems [70,91] and adhesion matrix, bead entrapment [77], agar plate growth [92], growth in microfluidic channels, gaseous separation [93], cell droplets [94], and matrix immobilization [95].…”
Section: Reactor Design and Available Technologies For Co-culturementioning
confidence: 99%